In‐Volume Laser Direct Writing of Silicon—Challenges and Opportunities. Issue 11 (26th September 2021) - Chambonneau, Maxime; Grojo, David; Tokel, Onur; Ilday, Fatih Ömer; Tzortzakis, Stelios; Nolte, Stefan
Abstract: Laser direct writing is a widely employed technique for 3D, contactless, and fast functionalization of dielectrics. Its success mainly originates from the utilization of ultrashort laser pulses, offering an incomparable degree of control on the produced material modifications. However, challenges remain for devising an equivalent technique in crystalline silicon which is the backbone material of the semiconductor industry. The physical mechanisms inhibiting sufficient energy deposition inside silicon with femtosecond laser pulses are reviewed in this article as well as the strategies established so far for bypassing these limitations. These solutions consisting of employing longer pulses (in the picosecond and nanosecond regime), femtosecond‐pulse trains, and surface‐seeded bulk modifications have allowed addressing numerous applications. Abstract : While in‐volume laser direct writing is a well‐established technique for functionalizing dielectrics, devising an equivalent for silicon is an uttermost challenge. Recent fundamental and applied studies lay the foundation for the 3D, fast, and contactless inscription of numerous functions inside this semiconductor. This review provides a comprehensive presentation of the limitations, solutions, and applications inherent to laser–silicon interaction.